Search for a fourth generation b '-quark at LEP-II at root s=196-209GeV - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2007)
A search for the pair production of fourth generation b'-quarks was performed using data taken by the DELPHI detector at LEP-II. The analysed data were collected at centre-of-mass energies ranging from 196 to 209 GeV, corresponding to an integrated luminosity of 420 pb-1. No evidence for a signal was found. Upper limits on BR(b'→bZ) and BR(b'→cW) were obtained for b' masses ranging from 96 to 103 GeV/c 2. These limits, together with the theoretical branching ratios predicted by a sequential four generations model, were used to constrain the value of RCKM = | Vtb′Vtb/Vcb′|, where V cb′, Vtb′ and Vtb are elements of the extended CKM matrix. © Springer-Verlag Berlin Heidelberg 2007.